2016
DOI: 10.1016/j.ijplas.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the residual topography to single crystal plasticity parameters in Berkovich nanoindentation on FCC nickel

Abstract: Fundamental deformation mechanisms of FCC materials under indentation have been probed at the grain scale. Experimental tests have been conducted on large-grained annealed and cold-worked polycrystalline nickel samples with a Berkovich indenter. Indentation axes have been chosen to be close to the three main crystallographic directions [001], [101] and [111]. Pileups and slip traces have been revealed around the residual imprints by analysing topographic measurements obtained by atomic force microscopy. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 68 publications
3
31
0
Order By: Relevance
“…The pile-up patterns depend on the grain orientation: Multiple triangles in the f111g grain, butterfly shapes in the f101g grain and the cross shape in f001g grain were also observed during previous studies [21,26,28,[44][45][46][47]. Wang et al [28] reported that the pile-up pattern on a 111 f g surface has a sixfold symmetry (threefold rotational symmetry and twofold mirror symmetry, which is the same as an equilateral triangle).…”
Section: Discussionmentioning
confidence: 63%
“…The pile-up patterns depend on the grain orientation: Multiple triangles in the f111g grain, butterfly shapes in the f101g grain and the cross shape in f001g grain were also observed during previous studies [21,26,28,[44][45][46][47]. Wang et al [28] reported that the pile-up pattern on a 111 f g surface has a sixfold symmetry (threefold rotational symmetry and twofold mirror symmetry, which is the same as an equilateral triangle).…”
Section: Discussionmentioning
confidence: 63%
“…So, the plastic zone around the imprints in the CG Cu cannot be confined by the GB structure in the UFG Cu and the pile-up lateral extension thus declines to som extent (as shown in Figure 8c). Additionally, Renner claimed that the pile-up sizes and distributions such as height and lateral extension depend on the crystallographic directions and indenter disorientation, which are also the main reasons for generating significant asymmetries around imprints in CG metals [11].…”
Section: Discussionmentioning
confidence: 99%
“…Taking the pile-ups of the residual impression into account, the projected area should be calibrated in order to yield relatively accurate values of E and H. A method exploiting the topography measurements to correct the values of these two mechanical parameters was proposed by Renner as the following procedures [11]:…”
Section: Correction To the Hardness And Modulus From Pile-up Measuremmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoindentation method has a very small measurement area. Therefore, it is expected to be able to measure the effect of the crystal orientation or microdefects of specimens on the mechanical properties of a material [3][4][5][6][7]. In this report, in order to investigate the effect of the crystal orientation, the hardness and the reduced modulus of the single crystal of sapphire were measured by changing the direction angle of Berkovich indenter.…”
Section: Introductionmentioning
confidence: 99%